2018
DOI: 10.1002/slct.201702186
|View full text |Cite
|
Sign up to set email alerts
|

Sulphated Zirconia Supported on Cordierite Honeycomb Monolith for Effective Synthesis of Solketal from Acetalisation of Glycerol with Acetone

Abstract: Liquid phase acetalisation of glycerol with acetone to synthesize a value added glycerol acetal (solketal) has been studied over solid oxides such as ZrO2, ZrO2‐Al2O3 and SO42−/ZrO2 coated on cordierite honeycomb monoliths. Such honeycomb monoliths were characterized by XRD, TPD‐NH3, BET, SEM and FTIR techniques. Characterization results indicate that the incorporation of calculated amounts of Al2O3 or SO42− on ZrO2 strongly influences the surface acidity of ZrO2, increases the catalytically active tetragonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Recently, we have reported the synthesis of solketal over sulfated zirconia, which took longer reaction times of 100 min (Vasantha et al, 2018). Mordenite and Amberlyst-35 have also been used as catalytic material (Priya et al, 2017;Nanda et al, 2016) and were active in the synthesis of solketal but showed marginal deactivation with time.…”
Section: Comparison Of the Catalytic Activity Of Other Catalysts In Tmentioning
confidence: 99%
“…Recently, we have reported the synthesis of solketal over sulfated zirconia, which took longer reaction times of 100 min (Vasantha et al, 2018). Mordenite and Amberlyst-35 have also been used as catalytic material (Priya et al, 2017;Nanda et al, 2016) and were active in the synthesis of solketal but showed marginal deactivation with time.…”
Section: Comparison Of the Catalytic Activity Of Other Catalysts In Tmentioning
confidence: 99%
“…One of the most promising routes involves the production of cyclic acetals from the condensation of gly and carbonyl As a result, the identification of simple and effective processes able to convert gly into value-added chemicals unveil tremendous potential and can give substantial contribution to the sustainability of the whole biodiesel industry [2,4]. One of the most promising routes involves the production of cyclic acetals from the condensation of gly and carbonyl compounds, with applications as fuel oxygenates or chemical intermediates [2,4,5]. Glycerol acetals can work as octane enhancer into regular gasoline, or can reduce particulate emissions of diesel fuel [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Monolithic structures pose an attractive alternative to conventionally prepared catalyst pellets or powders due to a number of superior properties. Monoliths can offer better mass transfer, a low pressure drop, thermal stability and good mechanical strength over conventional catalyst pellets or powders ,,,. For real industrial applications, catalysts are usually made into a shaped substrate rather than a powder state.…”
Section: Introductionmentioning
confidence: 99%
“…Monoliths can offer better mass transfer, a low pressure drop, thermal stability and good mechanical strength over conventional catalyst pellets or powders. [11,12,13,14] For real industrial applications, catalysts are usually made into a shaped substrate rather than a powder state. Cordierite (2MgO⋅2Al 2 O 3 ⋅5SiO 2 ) monolith is widely used as catalyst supports due to its low pressure drop, [15] superior thermal stability and high attrition resistance.…”
Section: Introductionmentioning
confidence: 99%